Sandstone characteristics and hydrocarbon exploration significance of the Middle-Lower Jurassic of the central-eastern part of the northern tectonic belt of the Kuqa Depression, Tarim Basin, China - Ronghu Zhang; Haijun Yang; Hongxing Wei; Chaofeng Yu; Zhao Yang; Jin Wu (Journal of Natural Gas Geoscience, 2020)
The Jurassic at the northern tectonic belt of the Kuqa Depression, Tarim Basin, is the key frontier of replacement for oil and gas exploration in the 13th five-year plan of China. The 4th national resource evaluation of China demonstrates that this area possesses resources amounting to 565 × 106 t of oil equivalent, and yet the proven resource accounts for only 3.7% of the total. To determine the exploration target of the Mid-Lower Jurassic and identify the favorable zone and trap type, studies on sedimentary microfacies and sand body configuration have been carried out based on data from outcrops, drilling, and well logging. It is clarified that the braided river delta plain-front-shore-shallow lake sedimentary system deposited during lake transgression in the wide and gentle lake basin occurs in the Middle and Lower Jurassic. The Ahe Formation is developed with the ultra-thick sand body of the large braided river channel in the braided river upper delta plain. Meanwhile, the Yangxia and Kezilenuer formations are found with the mid-thin sand body of the medium and small fluvial channel of the braided river lower delta plain-front sedimentation. There are three sand bodybuilding models favorable for hydrocarbon accumulation that has been developed. Moreover, it is proposed that the sand body of the Ahe Formation, originating from vertical accretion of the braided river channel upper delta plain fluvial, is the exploration zone for structural reservoirs; the lateral imbricated sand body of the braided river channel lower delta plain fluvial of the Yangxia Formation, and the lenticular sand body resulting from lateral accretion of the delta front fluvial channel of the Kezilenuer Formation, are the exploration zone for structural-lithological and lithological reservoirs. The Kezilenuer and Yangxia formations at the eastern, northern, and western flanks of the Tugeerming anticline are the most favorable for structural-lithological reservoirs, and a favorable zone of 700 km2 at the flanks has been demarcated. The platform zone at the Dibei slope is the most preferable for structural reservoirs, where in the average porosity of the Ahe Formation reservoir rock is 5.6%, the average permeability is 0.75 × 10−3μm2, and the favorable zone covers 750 km2. Solid evidence has been provided for the determination of the favorable zone and trap type in the Middle and Lower Jurassic at the northern tectonic belt of the Kuqa Depression.